Peran E-Commerce dalam Membuka Peluang Kewirausahaan Generasi Muda - Junaidi, Edi; Alifiah, Afsah; Haqiqi, Galih Anjani; Prasetyoningtyas, Ari Anggraini Winadi (Universitas Syiah Kuala, 2025)
The rapid growth of digital technology has given rise to e-commerce as a new medium that opens significant entrepreneurial opportunities for young generations. This paper aims to examine two main aspects: the role of e-commerce in fostering youth entrepreneurship and the legal challenges that accompany it. The study applies a normative legal writing method with statutory, conceptual, and case approaches, analyzing the experiences of young entrepreneurs such as Nicholas Kurniawan, Febrianto Eka Wijaya, Fitrah Kusumaningtyas, and Helianti Hilman. The findings reveal that e-commerce plays an important role in expanding market access, lowering entry barriers, encouraging innovation, strengthening collaboration, enhancing digital literacy, and creating new jobs. On the other hand, digital entrepreneurship also faces various legal challenges, including consumer protection, personal data protection, intellectual property rights, unfair competition, electronic contracts, and taxation obligations. Therefore, entrepreneurial opportunities in e-commerce must be balanced with legal awareness so that young generations can develop not only economically, but also sustainably and in compliance with the legal framework.